Resilience of persons with disabilities to climate induced landslide hazards in the vulnerable areas of Mount Elgon, Uganda - Ssennoga, Martin; Kisira, Yeeko; Mugagga, Frank; Nadhomi, Daniel (International Journal of Disaster Risk Reduction, 2022)
The resilience of persons with disabilities in landslide-prone areas is not well understood. Moreover, these disasters are persistent and this information is vital in enhancing socioeconomic transformation of the livelihoods of Persons with disabilities. We anchored the resilience of Persons with disabilities to landslide hazards on four factors, namely; risk exposure, socioeconomic capacity, the individual functioning capacity, and the individual's housing infrastructure. The objectives of the study were (i) to assess the level of resilience of Persons with disabilities to landslides and (ii) to explore the significant sociodemographic factors that underpin the resilience of Persons with disabilities to landslides. We used a cross-sectional design and snowball sampling to access the households respondents for interviews. The analysis included descriptive analysis and inferential statistics computed using in Statistical Package for Social Sciences (SPSS) Version 23 and Microsoft Excel version 2016. The geometric mean method was used to assess the level of resilience. The Chisquare and Kendals' Tau-b were used to ascertain the underpinning sociodemographic factors to the resilience of Persons with disabilities. Results revealed that the overall resilience was low. Sex, education level, and access to disaster training significantly controlled resilience among Persons with disabilities. We conclude that Persons with disabilities in landslideprone areas have low resilience and receive little attention with respect to rescue and recovery amidst these recurrent hazards in the area. There is a need to boost the resilience of Persons with disabilities, especially the housing infrastructure and functioning capacity taking into account their social networks to build the socioeconomic and preparedness wings of disaster resilience among Persons with disabilities.
openalex: W4292074941
Keywords: _z:class:countries; openalex:import; openalex:yes